CYP2C93(1075A > C), ABCB1 and SLCO1B1 genetic polymorphisms and gender are determinants of inter-subject variability in pitavastatin pharmacokinetics - Zhou, Quan; Chen, Qiu-Xia; Ruan, Zou-Rong; Yuan, Hong; Xu, Hui-Min; Zeng, Su (Pharmazie, 2013)
A pharmacokinetics study was conducted in 12 Chinese volunteers following a single dose of 1 mg, 2 mg and 4 mg of pitavastatin calcium in an open-label, randomized, three-period crossover design. Plasma concentrations of pitavastatin acid and pitavastatin lactone were determined by a HPLC method. Single-nucleotide polymorphisms (SNPs) in ABCB1, ABCG2, SLCO1B1, CYP2C9 and CYP3A5 were determined by TaqMan® (MGB) genotyping assay. An analysis was performed on the relationship between the aforementioned SNPs and dose-normalized (based on 1 mg) area under the plasma concentration-time curve extrapolated to infinity [AUC(0-∞)] and peak plasma concentration (Cmax) values of the acid and lactone forms of pitavastatin. Pitavastatin exhibited linear pharmacokinetics and great inter-subject variability. Compared to CYP2C9*1/*1 carriers, CYP2C9*1/*3 carriers had higher AUC(0-∞) and Cmax of pitavastatin acid and AUC(0-∞) of pitavastatin lactone (P < 0.05). With respect to ABCB1 G2677T/A, non-G carriers had higher Cmax and AUC(0-∞) of pitavastatin acid, and Cmax of pitavastatin lactone compared to GT, GA or GG genotype carriers (P < 0.05). Gene-dose effects of SLCO1B1 c.521T > C and g.11187G > A on pharmacokinetics of the acid and lactone forms were observed. Compared to non-SLCO1B1*17 carriers, SLCO1B1*17 carriers had higher Cmax and AUC(0-∞) of the acid and lactone forms (P < 0.05). Significant sex difference was observed for pharmacokinetics of the lactone. Female SLCO1B1 521TT subjects had higher Cmax and AUC(0-∞) of pitavastatin lactone compared to male 521TT subjects, however, such gender difference disappeared in 521TC and 521CC subjects. Pitavastatin pharmacokinetics was not significantly affected by ABCB1 C1236T, ABCB1C3435T, CYP3A5*3, ABCG2 c.34G > A, c.421C > A, SLCO1B1 c.388A > G, c.571T > C and c.597C > T. We conclude that CYP2C9*3, ABCB1 G2677T/A, SLCO1B1 c.521T > C, SLCO1B1 g.11187G > A, SLCO1B1*17 and gender contribute to inter-subject variability in pitavastatin pharmacokinetics. Personalized medicine should be necessary for hypercholesterolaemic patients receiving pitavastatin.